Influence of bleaching and desensitizing gel on bond strength of orthodontic brackets - Fernanda Alves Rodrigues Britto; Adriana Simoni Lucato; Heloisa Cristina Valdrighi; Sílvia Amélia Scudeler Vedovello (Dental Press Editora, 2015)
OBJECTIVE: The objective of this study was to assess, in vitro, the influence of bleaching gel and the use of desensitizing agent over bond strength of ceramic brackets bonded to bovine enamel. METHODS: One hundred bovine incisors were selected and randomly divided into five groups (n = 20): Group 1, control group (without bleaching); Group 2, bleached with 35% hydrogen peroxide; Group 3, bleached with 35% hydrogen peroxide (three applications, 15 minutes each) and desensitizing agent applied for 10 minutes; Group 4, bleached with 35% hydrogen peroxide for 40 minutes; Group 5, bleached with 35% hydrogen peroxide for 40 minutes with desensitizing agent applied for 10 minutes. Brackets were bonded 7 days after bleaching and submitted to shear bond strength test after 24 hours at a compression rate of 1 mm/minute. After fracture, the adhesive remnant index (ARI) was assessed under stereoscopic at 40 x magnification. Shear strength data (MPa) were submitted to one-way ANOVA and Tukey's test with significance level set at 5%. RESULTS: Group 5 (29.33 MPa) showed significantly higher bond strength than Group 1 (19.19 MPa), Group 2 (20.59 MPa) and Group 4 (23.25 MPa), but with no difference in comparison to Group 3. There was no significant difference among the other groups. The adhesive remnant index showed predominance of score 3, that is, all resin remained adhered to enamel for all groups. CONCLUSION: Bleaching with 35% hydrogen peroxide with calcium associated with desensitizing agent application produced higher bond strength values of brackets bonded to bovine enamel.